THE TECHNOLOGY OF FUTURE SOCIAL WORKERS’ SELF-EDUCATION - Maіboroda G. (Вісник Черкаського національного університету імені Богдана Хмельницького. Серія: "Педагогічні науки", 2017)
Introduction. An integral component of future social workers’ professional training is self-education. Namely self-education is determined by many researchers as a way and result of a specialist’s qualitative personal growth. Modern teachers of higher educational establishments as well as practitioners in the field of social sphere turn to scientists with questions about: 1) search of methods, techniques, technologies of an individual’s involvement to self-education; 2) increase of motivation to self-education activities; 3) reaching a high self-education level and so on. However, the lack of practical skills, inability to choose and use modern and efficient methods of self-education complicate this process and negatively affect its results. These issues require scientific-and-theoretical understanding, practical testing and grounding. Purpose. The urgent need for future social workers’ professional training at higher educational establishments is to create new ways of self-education; transfer of knowledge and forming skills that would provide an opportunity for students during their studies at a higher educational establishment to acquire independently modern information necessary for solving customers’ urgent problems, to use it for self-development and self-improvement. The topicality of the chosen theme is due to existing contradictions between: a) the need for continuous improvement of the process of students’ self-education and the lack of validity of methodological approaches to future social workers’ self-education; b) current requirements to a social worker’s professional activities and insufficient awareness of the role and place of self-education in future social workers professional training; c) the need of technologization of students’ self-education and traditional approach to its organization at higher educational establishments. Methods. By means of observations (direct and indirect), discussions, study of educational and methodical documentation, comparative analysis, which were carried out in the process of teaching and learning by students of subjects professionally oriented discipline training in practical departments; conducting educational and social work was singled out. The purpose of this article is to analyze the existing works on issues of future social workers’ self-education technology and development and justification of stages of the technology. Results. Self-education is a social process that is based, on the one hand, on demands of a society to a certain profession, and, on the other hand, it depends on the attitude of a professional to the requirements imposed by society to the profession. The process of self-education is a technology represented by several interrelated stages aimed at obtaining a guaranteed positive result. It is necessary to mention that the developed by us structure and content of the technology of future social workers’ self-education has three stages: initial, basic, final. The initial stage of the technology involves studying students’ needs as for self-education, identification of existing motives as for self-education (cognitive, activity, training, professional). The development and formation of motives to self-education is conducted by implementing a complex program "Students’ Self-Education". The program is implemented: a) during teaching subjects "Volunteerism in Ukraine", "Introduction to Speciality", "History of Social Work"; in the process of students’ adaptation to study at the University, a curator’s upbringing work, leisure activities, involvement of students in scientific-and-research work. With this aim an individual plan of a student’s self-education is developed. This stage lasts during the first year at a higher educational establishment. At the basic stage of the technology implementation of the program "Students’ Self-Education" and of an individual plan of self-education is continued. The issues of self-education are actualized at classes in such subjects as "Theory of Social Work," "An Individual’s Socialization", "Methods of Social Work", "Technologies of Social Work Foreign Countries". All students’ efforts are also directed at realization of theoretical knowledge and skills in the process of various types of practices. An important role in the implementation of the main stage plays the development of students’ creativity in all its forms as well as demonstration of acquired knowledge and skills of self-education and its results. This stage continues during the second and the third years of study at the University. The final stage of the technology involves self-control, self-correction, self-analysis and synthesis of the obtained by students results of self-education. Alongside with the mentioned above facts the process ofcontinuous improvement of acquired skills of self-education and their demonstration at competitions on sharing the experience is not interrupted. Conclusions. Implementation of the technology of future social workers’ self-education in the educational process of a higher educational establishment has a positive influence on the professional training of students. An important condition for the successful implementation of this technology We consider strict adherence to such principles of self-education as: complexity, systematicity, consistency, determination, independence, individuality, phasing, sequencing, relationship and completion of stages, analyticity, stimulation, efficiency.